(untitled) (Journal of Computational Mathematics, 1990)
The aim of this conjoint paper is to discuss the problem of the best rational approximation with interpolating constraints. In part I, we give the necessary and sufficient conditions for the existence of the best rational approximations and establish some characterization theorem for such approximations. The problems of uniqueness, the properties for the set of best approximations, strong uniqueness and continuity of best approximation operator are considered in Part II. The results obtained in this paper are the completion and extension of those given in [1].